3x-y=6
y=x-4
solve by substitution
3x-x+4=6
2x=2
x=1
Now that you know x, but in in the equation to find y (either equation will work)
y= 1-4
y= -3
now that you have both answers, let's check them.
3(-1) - (-3) =6
yes, it works....
Hopefully this makes sense!
Answer:
a + c = 80
a = 2c - 8
Step-by-step explanation:
Topic: Algebra
You can use expanded form: 4 X 700, 4 X 50, 4 X 4, = 3016.
You can use the Distributive Property of Multiplication: (4 X 500) + (4 X 254) = 3016.
Answer:
<h2>0, 3, 8, 15</h2>
Step-by-step explanation:
Substitute n = 1, n = 2, n = 3 and n = 4 to the equation f(n) = n² - 1:
f(1) = 1² - 1 = 1 - 1 = 0
f(2) = 2² - 1 = 4 - 1 = 3
f(3) = 3² - 1 = 9 - 1 = 8
f(4) = 4² - 1 = 16 - 1 = 15
Hi there,
X x (-2) x 2 = 4 x (-2)
- x = - 2
Hence, X = 2
Hope this helps :)